2023
DOI: 10.3390/agronomy13020392
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of Microbial Residues within Aggregates of Fluvo-Aquic Soil under Biochar Application

Abstract: The use of biochar as a soil amendment has substantial potential to enhance soil quality and carbon sequestration. However, the responses to the addition of biochar based on soil microbial residues are not well understood, particularly at the aggregate level. Herein, a two-year field experiment investigated the characteristics of distribution of microbial residues in calcareous fluvo-aquic soil aggregates (SA) in Henan Province, China. Four treatments were established as follows: no fertilizer (CK), chemical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Thus, fungal and bacterial necromass C was notably greater in macro‐aggregates (Figure 1). This result is consistent with previous studies by Ding et al (2015) and Cheng et al (2023). Greater microbial necromass in macro‐aggregates is crucial for the SOC capacity to serve as a dynamic source repository because macro‐aggregates are the most dynamic (Ding et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, fungal and bacterial necromass C was notably greater in macro‐aggregates (Figure 1). This result is consistent with previous studies by Ding et al (2015) and Cheng et al (2023). Greater microbial necromass in macro‐aggregates is crucial for the SOC capacity to serve as a dynamic source repository because macro‐aggregates are the most dynamic (Ding et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…Ding et al (2015) andCheng et al (2023). Greater microbial F I G U R E 4 Effects of tillage practices on microbial biomass C (a, b), dissolved organic C (c, d), and permanganate oxidizable C (e, f) in aggregates.…”
mentioning
confidence: 99%
“…To date, only seven studies have explored the effects of BC on MNC accumulation, and none have investigated the effects of microplastics. Most of these studies have reported that BC increases the content of amino sugars and MNC .…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of engineered C materials (e.g., BC and microplastics) inevitably influences the composition and stability of the soil C pools. Typically, a single application of BC increases MNC accumulation by 10–20%, whereas multiple BC applications over a decade-long time frame have been reported to increase MNC by 21–59% . However, some studies have reported a decrease in amino sugar and MNC contents following BC addition.…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue consists of four subjects centered around "Biochar for Sustainable Farming and Recultivation". These subjects are: (1) the research progress of biochar in carbon sequestration and emission reduction [5]; (2) the consequences of biochar application on soil aggregation [6,7]; (3) the influence of biochar addition on the humification process of organic wastes [8]; and (4) the effects of biochar addition on soil organic carbon transformation and composition [9]. This Special Issue covers both theoretical mechanisms and practical applications, including laboratory incubations and field experiments.…”
Section: Special Issue Overviewmentioning
confidence: 99%